1994
DOI: 10.1159/000261638
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in Experimental Dental Caries in Four Inbred Strains of Rats

Abstract: The relative contribution of the host genetic effect on the susceptibility to dental caries was examined. Four inbred strains of male rats (BN/Sea, F344/Ms, PVG/ cSea, and WKA/Sea) were inoculated with Streptococcus mutans and fed a cariogenic diet. The caries scores of the molar teeth were compared among these four strains, and the degree of genetic determination was estimated by analysis of variance. Statistically significant differences in caries scores were found among these strains (F344 > WKA > PVG/c > B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
(9 reference statements)
1
4
0
Order By: Relevance
“…Our study revealed that children who have a familial history of dental caries are more at risk (OR 8.2) of dental caries. A similar association was reported by various other authors [ 90 , 91 , 92 ]. A correlation of dental decay in siblings was observed by Klein and Palmer (1938) [ 93 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our study revealed that children who have a familial history of dental caries are more at risk (OR 8.2) of dental caries. A similar association was reported by various other authors [ 90 , 91 , 92 ]. A correlation of dental decay in siblings was observed by Klein and Palmer (1938) [ 93 ].…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, to date, there is little literature describing the direct effects of AMPs on dental caries. Prior to clinical trials, the well-established rat model is widely used for its favourable susceptibility to caries akin to that of humans, with the small body size of rats optimizing operations and a high reproducibility [22,23]. In addition, the physicochemical properties and macromolecular composition of saliva could influence microbial colonization [24,25] and the maintenance of antibacterial agents [26] both in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…At this stage, the main strategies are experimental: application of animal models and controlled crossbreeding, and observational: applicable to human populations, such as familial aggregation and twin studies. Typically, animal studies use inbred strains presenting extreme known phenotypes to analyze the result of controlled crossing, correlating genotypes and phenotypes (Kanamoto et al , 1994). Familial aggregation analysis investigates the clustering of disease cases in large pedigrees resulting from excessive sharing of genetic and/or environmental variants (Burton et al , 2005; Hopper et al , 2005).…”
Section: Genetic Analysis Of Complex Traitsmentioning
confidence: 99%
“…Genetic studies have been conducted to better comprehend the genetic component associated with the individual susceptibility to dental decay development. The approaches which have been used include: (i) experimental studies involving animal models and controlled crossbreeding (Hunt et al , 1944, 1955; Kanamoto et al , 1994); (ii) observational studies involving human populations, such as familial aggregation analysis (Garn et al , 1976a) and twin studies (Finn and Caldwell, 1963; Boraas et al , 1988; Conry et al , 1993; Sofaer, 1993; Hassel, 1995; Shuler, 2001), and (iii) linkage and association studies (Slayton et al , 2005; Bagherian et al , 2008; Deeley et al , 2008; Patir et al , 2008; Vieira et al , 2008).…”
Section: Genetic Analysis Of Dental Cariesmentioning
confidence: 99%
See 1 more Smart Citation